Longitudinal alterations in gamma-aminobutyric acid (GABAA) receptor availability over ∼ 1 year following traumatic brain injury. Issue 4 (15th June 2022) - Kang, Y; Jamison, K; Jaywant, A; Dams-O'Connor, K; Kim, N; Karakatsanis, N A; Butler, T; Schiff, N D; Kuceyeski, A; Shah, S A
Abstract: Longitudinal alterations of gamma-aminobutyric acid (GABAA ) receptor availability following traumatic brain injury have remained uncharacterized and may reflect changes in neuronal structure and function linked to cognitive recovery. We measured GABAA receptor availability using the tracer [11C]flumazenil in nine adults with traumatic brain injury (3–6 months after injury, subacute scan) and in 20 non-brain-injured individuals. A subset of subjects with traumatic brain injury (n = 7) were scanned at a second chronic time-point, 7–13 months after their first scan; controls (n = 9) were scanned for a second time, 5–11 months after the first scan. After accounting for atrophy in subjects with traumatic brain injury, we find broad decreases in GABAA receptor availability predominantly within the frontal lobes, striatum, and posterior-medial thalami; focal reductions were most pronounced in the right insula and anterior cingulate cortex (p < 0.05). Greater relative increase, compared to controls, in global GABAA receptor availability appeared between subacute and chronic scans. At chronic scan (>1 year post-injury), we find increased pallidal receptor availability compared to controls. Conversely, receptor availability remained depressed across the frontal cortices. Longitudinal improvement in executive attention correlated with increases in receptor availability across bilateral fronto-parietal cortical regions and the anterior-lateral aspects of the thalami. The specific observations of persistent bi-frontal lobe reductions and bilateral pallidal elevation are consistent with the anterior forebrain mesocircuit hypothesis for recovery of consciousness following a wide range of brain injuries; our results provide novel correlative data in support of specific cellular mechanisms underlying persistent cognitive deficits. Collectively, these measurements support the use of [11C]flumazenil to track recovery of large-scale network function following brain injuries and measure response to therapeutics. Abstract : Kang et al . report that following traumatic brain injury, decreased GABAA receptor availability is seen in the anterior forebrain mesocircuit. Recovery during the ∼1 year post is marked by widespread increases, especially in the pallidum, but remains depressed across the frontal cortices possibly contributing to enduring cognitive impairments. Graphical Abstract: Graphical abstract